Answer: i eat fooood bro
Step-by-step explanation:
Answer:
17900
Step-by-step explanation:
First term a = -19
common difference d = -15-(-19) = 4
number of terms, n = 100
sum of first 100 terms,
n/2(2a+(n-1)d)
= 100/2(2×(-19)+(100-1)4)
= 50×(-38+99×4)
= 50×358
= 17900
Rewrite = so is on the left side.
Answer:
-
Step-by-step explanation:
becuase (-3)(-4) will give you a positive and when you mutipy it with the 5 and 6 you will still get postive but when you multiply with -7, you will get a negitive
Answer: B. 77
Sub x =6 into the given expression
4x^2 - 12x + 5
= 4(6)^2 - 12(6) + 5
= 144 - 72 + 5
= 77